Application Of Break Even Point (Bep) In Determining Profit Planning At Pt. Panorama Sentra Wisata Tbk - Fahruddin Ahwal, Ikhwan; Ruzikna, Ruzikna; Mandataris , Mandataris (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Break Even Point (BEP) analysis with profit planning has a strong relationship and can help companies determine optimal sales targets so that the company's goal of achieving maximum profits can be met. PT. Panorama Sentrawisata Tbk is a company that has gone public, it is hoped that the profits obtained will attract investors to invest in the company. For this reason, it is necessary to analyze the application of BEP in determining profit planning at PT. Panorama Sentrawisata Tbk. This research is quantitative with a descriptive approach. The data used in this research is secondary data. The data analysis method uses the BEP analysis tool which is equipped with MoS analysis. The level of data analysis carried out starts from cost classification, BEP analysis, and margin of safety. The research results obtained in achieving the 2023 profit plan of 80 billion are by selling a minimum of IDR. 2.727.418.455,56, with a Margin of safety or decline in sales that can be tolerated so that the Company is at the break-even point that it does not experience losses of IDR. 888,888,888.89 or 33%.